Should the State Control Tariffs? - Zaid, Zaid; Dawaki, Farouk Aisha; Ololade, Sabit Kazeem (Universitas Muhammadiyah Yogyakarta, 2021)
Tariffs or price control has been a controversial subject in recent years. The debate between legal experts and economists is still a hot topic in any discussion. Tariff control regulated in the work creation omnibus law seems to be a topic that must be discussed again regarding this regulation’s urgency. Are specific prices so impressive that the government can intervene in regulating them? This article examines the urgency of rules regarding price controls to create a healthy competitive environment. After conducting a critical literature review, it was analyzed with critical analysis and looking at the objective of competition law was to maximize welfare by protecting competition. The results in this article indicated that the government could only intervene in regulating price-fixing only if companies’ pricing could harm the country’s economy and consumer welfare. The government, therefore, had an interest in regulating the price ceiling. Meanwhile, the price floor, which was believed to be pro-consumer and could promote consumer welfare had no interest and should not have been limited by the government.